2014
DOI: 10.18632/oncotarget.3059
|View full text |Cite
|
Sign up to set email alerts
|

DCLK1 is a broadly dysregulated target against epithelial-mesenchymal transition, focal adhesion, and stemness in clear cell renal carcinoma

Abstract: Renal clear cell carcinoma (RCC) is the most common type of kidney cancer and the 8th most common cancer overall in the US. RCC survival rates drop precipitously with regional and distant spread and recent studies have demonstrated that RCC presents an epithelial-mesenchymal transition (EMT) phenotype linked to increased recurrence and decreased survival. EMT is a key characteristic of tumor stem cells (TSCs) along with chemo-resistance and radio-resistance, which are also phenotypic of RCC. Targeting these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
120
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(135 citation statements)
references
References 37 publications
15
120
0
Order By: Relevance
“…Several cancers have been shown to possess an EMT phenotype that is linked with resistance to conventional chemotherapies (Hollier et al, 2009;Keitel et al, 2014;Weygant et al, 2015). In our study, the expression of fibronectin and vimentin and nuclear translocation of b-catenin were increased in 786-O cells treated with sunitinib.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several cancers have been shown to possess an EMT phenotype that is linked with resistance to conventional chemotherapies (Hollier et al, 2009;Keitel et al, 2014;Weygant et al, 2015). In our study, the expression of fibronectin and vimentin and nuclear translocation of b-catenin were increased in 786-O cells treated with sunitinib.…”
Section: Discussionsupporting
confidence: 53%
“…Several recent studies showed that cells that have undergone epithelial-mesenchymal transition (EMT) are relatively resistant to conventional chemotherapies (Hollier et al, 2009;Keitel et al, 2014;Weygant et al, 2015). Sánchez-Tilló demonstrated that the expression of E-cadherin is associated with a high sensitivity to the epidermal growth factor receptor (EGFR) inhibitor gefitinib (Witta et al, 2006;Sánchez-Tilló et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 EMT is also correlated with an advanced recurrence risk and poor overall survival in patients with RCC. 37 Moreover, our data demonstrated that LDHC could upregulate the expression of MMP-9. This protein was a member of the family of zinc-dependent endopeptidases, the central role of which was the degradation and remodelling of the extracellular matrix, leading to tumour invasion and metastasis.…”
mentioning
confidence: 56%
“…Again, siRNA-mediated knockdown of Dclk1 led to a significant inhibition of tumor cell proliferation, focal adhesion, invasion and clonogenic growth. 18 However, some of the strongest data on tumor growth can be found in models of pancreatic cancer. Sureban and colleagues extended our knowledge on Dclk1 function in cancer through a series of well-designed experiments in mouse models of pancreatic cancer and pancreatic cancer cell lines.…”
Section: Functional Relevance Of Dclk1 Expression In Malignancymentioning
confidence: 99%